Practical Activity Model to Form Religious Values in the Congregation of the "Healthy Youth" Community in Indramayu Regency - Abdul Somad; Nurkholis Majid; Suhendi Suhendi (International Journal of Nusantara Islam, 2026)
The importance of developing religiosity among young people presents a unique challenge in the modern era, which is filled with global influences and declining moral values. Religious values cannot develop quickly but require a process appropriate to the community's context and characteristics. This study aims to identify and evaluate the practical activity patterns implemented by the "Healthy Youth" group to build and strengthen religious values among rural youth. In addition, this study aims to identify the types of religious values that emerge from community activities and to examine the challenges and negative impacts that arise during their implementation. This study employs a descriptive qualitative method, collecting data through observation and in-depth interviews. The data analysis process is carried out interactively through steps such as data reduction, data presentation, and drawing conclusions, with validity strengthened through source triangulation. The study shows that the practical activity model in the "Healthy Youth" community can strengthen rural youth's religious values ​​. This model focuses on real social problems, uses flexible studies, actively involves members, and carries out socio-religious activities together. Religious values are strengthened through exemplary sources and approaches appropriate to the context. These activities fostered important values ​​such as sincerity, Islamic brotherhood, knowledge sharing, responsibility, tolerance, and consistency in worship. However, the research also identified obstacles, including a lack of ethical boundaries in discussions, minimal supervision, a lack of standardized materials, dependence on specific figures, excessively long activity durations, and the potential for symbolic polarization within the community.